The impact of ESG ratings on the market performance of commodity stock sector before and during the COVID-19 pandemic - Gawęda, Adrian; Złoty, Marcin (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The growing importance of ESG in the international economy makes the analysed issues extremely interesting. More and more studies show the growing role of ESG performance on company financial and market results as well as analyse the impact of the COVID-19 pandemic on the financial market. The study of rate of return and the relationship between the largest company companies in European Union Member States is of key importance considering the investment portfolio risk. Aim: The main aim of the article is impact assessment of ESG performance of the firm (proxied by ESG scoring by Refinitiv) on the rate of return of commodity sector companies listed on financial markets of European Union Member States. The second goal of the paper is to determine the impact of the COVID-19 pandemic on the rate of return of the analysed companies. The third and final goal is to assess the impact of sector leader status on the rate of return of these companies (i.e. KGHM, PKN Orlen, Royal Dutch Shell and Rio Tinto). Results: ESG disclosure by the surveyed companies and ESG scoring had negative impact on the rate of return, while E, S and G scorings did not affect rate of return at all. Sector leaders were less negatively impacted by the COVID-19 economic crisis than the rest of the sector, however sector leadership status was not statistically significant. COVID-19 pandemic positively influenced the rate of return of analysed companies. In case of commodities stock companies, the economic crisis caused by the pandemic brought about higher levels of uncertainty in the financial markets.